Comprehending mission: the questions, methods, themes, problems, and prospects of missiology - Skreslet, Stanley H. (American Society of Missiology series, 2012)
Who studies Christian mission and why? -- Bible and mission -- History of mission -- Theology, mission, culture -- Christian mission in a world of religions -- The means of mission -- Missionary vacation